The Influence of Employer Branding and E-Recruitment on Job Application Intention Among Generation Z: The Mediating Role of Corporate Reputation and Moderating Role of Social Media Use - Yuspita, Agata; Malini, Helma; Syahbandi; Jaya, Arman; Fauzan, Rizky (Ilomata International Journal of Management, 2025)
This research investigates the impact of employer branding, e-recruitment, and corporate reputation on job applicants' intention to apply, with social media usage as a moderating variable. In a competitive digital landscape, understanding how these factors influence job seekers' behavior is crucial for companies aiming to attract top talent. Based on a sample of 203 respondents and measured using Partial Least Squares Structural Equation Modeling (PLS-SEM), the study demonstrates that both employer branding and e-recruitment positively and significantly influence the intention to apply. Corporate reputation is crucial in determining applicants' decisions, and social media activity strengthens the correlation between the intention to apply for jobs and the company's reputation. These results imply that businesses should prioritize employer branding and actively manage their digital presence, particularly on social media, to better engage with and attract potential job applicants.